Chemical Constituents of Canarium album - Xiang Zhao, Bao; Guang, Hui Jing; Zhong, Tang Qu; Xing, Gao; Lin, Sen Heng (Asian Journal of Chemistry, 2012)
The n-butanol fraction of the dried fruits of Canarium album was isolated and purified by means of chromatography. Four compounds were obtained and their structures were identified by spectral analysis as quercetin -3-O-a-L-rhamnoside (1), rutin (2), quercetin-3-O-b- D-glucoside (3) and 2a, 3a, 19a, 24-tetrahydroxyurs-12-en-28-oic acid -28-O-b-D-glucoside (4). Compounds 1, 2 and 4 have not been reported before from the fruit of Canarium album, compound 4 is the first triterpenoid saponin isolated from this plant source.